Evaluating the Association of Clinical Factors With Symptomatic Recurrence of Idiopathic Subglottic Stenosis - Menapace, Deanna C. (JAMA Otolaryngol Head Neck Surg, 2019)
IMPORTANCE: Idiopathic subglottic stenosis (iSGS) is a progressive and potentially life-threatening condition with very few targeted treatment options. OBJECTIVE: To characterize the clinical factors of patients with iSGS, including body mass index (BMI, calculated as weight in kilograms divided by height in meters squared), and evaluate their association with iSGS symptomatic recurrence. DESIGN, SETTING, AND PARTICIPANTS: This retrospective medical record review included 186 adult patients with iSGS treated at a single tertiary referral center between January 1, 1989, and December 31, 2015. All data analysis took place from January 1, 2018 to June 30, 2018. MAIN OUTCOMES AND MEASURES: The 3 BMI categories were examined for their association with iSGS recurrence. Outcome measurements included time to first symptomatic recurrence (TTFR) and recurrence-free survival (RFS). Comorbidities were recorded. RESULTS: Of the 186 patients in the study, 182 (98%) were women; mean (interquartile range) patient age, 49 (41-60) years. At iSGS diagnosis, 65 (35%) patients were underweight or normal weight; 45 (24%) were overweight; and 76 (41%) were obese (class 1, 2, or 3). Median BMI was 27.4. Ninety-one patients experienced TTFR at a median of 14 months. Compared with underweight or normal-weight patients, the hazard ratios for the associations of overweight, obese class 1, and obese class 2/3 patients with recurrence were 1.14 (95% CI, 0.65-1.99), 1.74 (95% CI, 1.04-2.93), and 1.04 (95% CI, 0.54-1.99), respectively. No differences in concomitant medical treatment regimens were found. While several comorbidities (gastroesophageal reflux disease, hypertension, hyperlipidemia, and diabetes mellitus) were associated with increasing BMI, they were not associated with iSGS symptomatic recurrence on multivariable analysis. CONCLUSIONS AND RELEVANCE: Results of this retrospective review show that class 1 obesity was associated with an increased rate of iSGS symptomatic recurrence compared with underweight or normal-weight patients. This association was not seen in class 2 or class 3 obesity. Patients with class 1 obesity should be counseled about this risk to aid in the assessment and management of symptoms.